Micro strip FED SIW venus shaped slot antenna for millimeter wireless communication applications - Kumar M, Nanda; Shanmuganantham, T (International Journal of Engineering and Technology, 2018)
SIW is an excellent technology for millimeter frequency range of applications. In this paper, introduced SIW Venus shaped slot antenna for 60 GHz frequency applications, it is useful for millimeter wireless communication applications. The proposed structure is intended with help of Rogers substrate Îµ_(r) = 2.2 and thickness of substrate is 0.381mm. Computer simulation technology (CST) studio suite is used for designing of proposed structure and obtained impedance bandwidth of 4.49 GHz with a resonant frequency of 60 GHz, their reflection coefficient is -27.576 dB. The simulation results like VSWR, gain, radiation pattern and efficiencies are observed for above proposed antenna. Finally introduces the RLC lumped equivalent circuit model for proposed antenna, that can be developed with the help of MATLAB, it generated reflection coefficient and VSWR results and it is perfectly matched with proposed antenna reflection coefficient and VSWR results.Â Â